Investigating Ideomotor Cognition with Motorvisual Priming Paradigms: Key Findings, Methodological Challenges, and Future Directions - Thomaschke, Roland (Frontiers in Psychology, 2012)
Ideomotor theory claims that perceptual representations of action effects are functionally involved in the planning of actions. Strong evidence for this claim comes from a phenomenon called motorvisual priming. Motorvisual priming refers to the finding that action planning directly affects perception, and that the effects are selective for stimuli that share features with the planned action. Motorvisual priming studies have provided detailed insights into the processing of perceptual representations in action planning. One important finding is that such representations in action planning have a categorical format, whereas metric representations are not anticipated in planning. Further essential findings regard the processing mechanisms and the time course of ideomotor cognition. Perceptual representations of action effects are first activated by action planning and then bound into a compound representation of the action plan. This compound representation is stabilized throughout the course of the action by the shielding of all involved representations from other cognitive processes. Despite a rapid growth in the number of motorvisual priming studies in the current literature, there are still many aspects of ideomotor cognition which have not yet been investigated. These aspects include the scope of ideomotor processing with regard to action types and stimulus types, as well as the exact nature of the binding and shielding mechanisms involved.